2014
DOI: 10.1186/s13049-014-0061-3
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and opportunities in assessing calls to emergency medical communication centre - a qualitative study

Abstract: IntroductionPrevious studies have described the difficulties and the complexity of assessing an emergency call, and assessment protocols intended to support the emergency medical dispatcher’s (EMD) assessment have been developed and evaluated in recent years. At present, the EMD identifies about 50-70 % of patients suffering from cardiac arrest, acute myocardial infarction or stroke. The previous research has primarily been focused on specific conditions, and it is still unclear whether there are any overall f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 20 publications
5
26
1
1
Order By: Relevance
“…Dispatchers in this study had a large proportion of calls with language barriers, but dispatchers specifically indicated that language barriers were not a barrier to effective dispatch and interpreter services were not used. 25 Another review of calls with language barriers, as compared to matched language-concordant calls, found longer dispatch times with much of the difference in dispatch times attributable to connecting to the telephonic interpreter service. However, the subset of calls with language barriers in which telephonic interpretation was used was not analyzed to measure whether use of telephonic interpreters was associated with more accurate dispatch.…”
Section: Resultsmentioning
confidence: 99%
“…Dispatchers in this study had a large proportion of calls with language barriers, but dispatchers specifically indicated that language barriers were not a barrier to effective dispatch and interpreter services were not used. 25 Another review of calls with language barriers, as compared to matched language-concordant calls, found longer dispatch times with much of the difference in dispatch times attributable to connecting to the telephonic interpreter service. However, the subset of calls with language barriers in which telephonic interpretation was used was not analyzed to measure whether use of telephonic interpreters was associated with more accurate dispatch.…”
Section: Resultsmentioning
confidence: 99%
“…In agreement with our findings, linguistic barriers to communication among Danish [31] and American [32, 33] immigrants have been found to be associated with less use of prehospital services for medical advice or assistance, particularly by telephone. Accordingly, the use of telephone healthline by non-native inhabitants in Sweden has been claimed to complicate medical decision-making [34], and multilingual telephone operator services have been proposed to meet this challenge [32]. Communication problems and lack of confidence have also been reported as major healthcare obstacles by non-native parents in Sweden [35].…”
Section: Discussionmentioning
confidence: 99%
“…, Lindstrom et al . ) indicating that the findings most likely could be applied in other settings even internationally.…”
Section: The Studymentioning
confidence: 91%